Rancang Bangun Sistem Informasi Pengajuan Surat Fakultas Teknik Universitas Udayana Berbasis Website menggunakan Metode Scrum - Dwik Andarilas Sibuea; I Nyoman Natha Pratama; David Samuel Sitorus; I Made Arsa Suyadnya; Adi Panca Saputra Iskandar; Komang Sri Utami (UNIVED Press, 2025)
Fakultas Teknik Universitas Udayana (FT UNUD) still uses a manual system for letter submission, resulting in delays in delivering information to students and increasing the workload of administrative staff. Additionally, this manual system often causes errors in record-keeping and makes it difficult to track the submission status. To address this issue, the Sistem Informasi Pengajuan Surat (SIPS), a web-based letter submission system integrated with SIMAK-NG, was developed using the Scrum method. The development was carried out iteratively through several sprints, covering requirements analysis, system design, implementation, testing, and evaluation. Testing using the Black Box Testing method showed that all features in SIPS functioned according to the designed specifications. With this system, the letter submission process is expected to become faster, more structured, and more efficient. Moreover, SIPS allows students to monitor the status of their submissions in real-time, enhancing the transparency of administrative services. SIPS also supports document digitalization, helping to reduce paper usage and improve the effectiveness of academic data management. However, further evaluation is needed to assess the system's impact on operational efficiency and user satisfaction to ensure the optimization of academic services at FT UNUD. In the future, this system can continue to be developed with additional features, such as automated notifications and integration with other academic services.